Developing and pilot testing ASTHMAXcel, a mobile app for adults with asthma. (3rd June 2021) - Hsia, Brian; Mowrey, Wenzhu; Keskin, Taha; Wu, Sammy; Aita, Rohit; Kwak, Lily; Ferastraoarou, Denisa; Rosenstreich, David; Jariwala, Sunit P.
Abstract: Objective: We sought to compare the impact of ASTHMAXcel, a novel, guideline-based, patient-facing mobile app to human-delivered asthma education. Methods: We conducted a focus group with asthma patients in the Bronx to identify desired mobile app features. ASTHMAXcel was designed based on patient feedback and consistent with NAEPP, BTS/SIGN, and GINA guidelines. The app was reviewed by internists, allergist/immunologists, and pulmonologists specializing in asthma treatment, asthma educators, and a behavioral scientist, and iteratively refined. The refined version of ASTHMAXcel was administered once via tablet at our outpatient Montefiore Asthma Center (MAC). Asthma knowledge was measured through the Asthma Knowledge Questionnaire (AKQ) pre and post-intervention. We also recorded process outcomes including completion time and patient satisfaction. In parallel, human-delivered education was delivered once at MAC. These outcomes were similarly collected. Results: 60 patients were enrolled with 30 in the ASTHMAXcel and 30 in the human-educator group. Mean AKQ in the ASTHMAXcel group vs human-educator group pre-intervention was 9.9 vs 10.5, p  = 0.27. Mean AKQ post-intervention in the ASTHMAXcel group vs human-educator group was 12.3 vs 14.4, p  = 0.0002. The mean AKQ improvement for both groups were 2.4 vs 3.9, p  = 0.007. Patients were highly satisfied in the ASTHMAXcel group scoring on average 27.9 out of 30 maximum points on the satisfaction survey. There was no difference in satisfaction scores or completion times (minutes) of either intervention. Conclusion: ASTHMAXcel was associated with an increase in AKQ, but the human-educator group experienced a greater improvement. ASTHMAXcel demonstrated no differences in process outcomes vs human-delivered education.